Paving the Path Toward Retirement for Assistance Animals: Transitioning Lives - Ng, Zenithson; Fine, Aubrey (Frontiers in Veterinary Science, 2019)
Assistance animals play significant roles in human therapy and well-being and represent a rapidly growing demographic of animals in society. Most research in the field of assistance animals has been focused on the effect of these animals on people. Only recently has there been a growing interest in the welfare and well-being of these animals and the effect of the work on the animals themselves. The concept of retirement, or withdrawing the animal from its working life, is an important welfare consideration that has received minimal discussion in the scientific literature. The notion of retirement is typically regarded as a reward earned after a lifetime of work, but this inevitable phase of an animal’s working life has positive and negative implications for both animal and handler. Some of these implications include recognizing the emotional impact of this life-altering event on both animal and handler. The decisions of when and how to appropriately retire an animal are typically made at the discretion of the assistance animal agencies and handlers, but standard evidence-based guidelines for the proper retirement of assistance animals are currently unavailable. This review will provide considerations and recommendations for the retirement that assistance animals deserve.